Dexmedetomidine for the prevention of postoperative delirium in patients after intracranial operation for brain tumours (DEPOD study): a study protocol and statistical plan for a multicentre randomised controlled trial - Hongqiu Gu; Linlin Zhang; Jian-Xin Zhou; Xuan He; Kun-Ming Cheng; Xin Qu; Yuan Xu; Penglin Ma (BMJ Open)
Introduction Postoperative delirium (POD) is prevalent in patients after major surgery and is associated with adverse outcomes. Several studies have reported that dexmedetomidine, a highly selective α2-adrenergic receptor agonist, can decrease the incidence of POD. However, neurosurgical patients are usually excluded from previous studies. The present study was designed to investigate the impact of prophylactic use of low-dose dexmedetomidine on the incidence of POD in patients after intracranial operation.Methods and analysis This is a multicentre, randomised, double-blinded and placebo-controlled trial. Seven hundred intensive care unit admitted patients after elective intracranial operation for brain tumours under general anaesthesia are randomly assigned to the dexmedetomidine group or the placebo group with a 1:1 ratio. For patients in the dexmedetomidine group, a continuous infusion of dexmedetomidine will be started at a rate of 0.1 μg/kg/hour immediately after enrolment on the day of operation and continued until 08:00 on postoperative day 1. For patients in the placebo group, normal saline will be administered at the same rate as in the dexmedetomidine group. The patients will be followed up for 28 days after enrolment. The primary endpoint is the incidence of POD, which is assessed two times per day using the Confusion Assessment Method for the intensive care unit (ICU), during the first 5 postoperative days. The secondary endpoints include the incidence of dexmedetomidine-related adverse events and non-delirium complications, the length of stay in the ICU and hospital and all-cause 28-day mortality after the operation.Ethics and dissemination The study protocol was approved by the Institutional Review Board of Beijing Tiantan Hospital Affiliated to Capital Medical University (No KY2019-091-02) and registered at ClinicalTrials.gov. The results of the trial will be presented at national and international conferences relevant to subject fields and submitted to international peer-reviewed journals.Trial registration number Trial registration number: NCT04399343; Pre-results.